2017
DOI: 10.1039/c7ra06222b
|View full text |Cite
|
Sign up to set email alerts
|

Research on cellulose nanocrystals produced from cellulose sources with various polymorphs

Abstract: Properties of CNCs obtained from cellulose with various polymorphs were investigated and compared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
150
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 418 publications
(222 citation statements)
references
References 36 publications
24
150
1
1
Order By: Relevance
“…The presence of two endothermic peaks confirmed that the sulfuric acid hydrolysis impacted the thermal stability of unmodified CNCs …”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The presence of two endothermic peaks confirmed that the sulfuric acid hydrolysis impacted the thermal stability of unmodified CNCs …”
Section: Resultsmentioning
confidence: 89%
“…The presence of two endothermic peaks confirmed that the sulfuric acid hydrolysis impacted the thermal stability of unmodified CNCs. 35 The first peak observed between 250 and 300 8C was small and the second peak which dominated the overall process occurred between 290 and 350 8C. The first peak was related decomposition of the negatively charged sulfate groups on CNCs and the second peak can be related to depolymerization of cellulose in competition with dehydration.…”
Section: Thermal Stabilitymentioning
confidence: 92%
“…Figure 3 (a) shows the XRD pattern of alpha cellulose that is highly amorphous as exhibited by the low intensity of peak at 22.5 o angular position of 2θ and it represents cellulose I structure. This amorphous region defines more disordered structure which means low crystal region as well as low degree of crystallinity [19,20]. Figure 3 [19].…”
Section: X-ray Diffraction (Xrd)mentioning
confidence: 99%
“…XRD pattern of the initial OPEFB-MCC was shown in Figure 1 (a) -(b). The crystalline structure was cellulose II showing its reflections around 2θ= 12, 20 and 22 [10,11]. After 4 h mechanical grinding course, the original fibrous MCC was converted into the aggregated globular particles resulting in decrease of the crystalline index (CrI).…”
Section: Morphological Changesmentioning
confidence: 99%
“…Measurements were recorded at room temperature over the 2θ range 3-50°, with a 0.02° step size. The crystallinity and the crystallite size were calculated using previous method in [10].…”
Section: Xrd Analysismentioning
confidence: 99%